2018
DOI: 10.21043/jobe.v1i1.3533
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Komik Manga Biologi Berbasis Android Untuk Peserta Didik Kelas Xi Ditingkat SMA/MA

Abstract: Pada pembelajaran biologi sarana dan prasarana penunjang pembelajaran serta perkembangan teknologi seperti android milik peserta didik belum dijadikan media pembelajaran. Alternatifnya dengan mengembangkan media pembelajaran komik manga digital berbasis android untuk memudahkan pemahaman materi biologi. Penelitian ini bertujuan untuk: 1.) Mengetahui cara pengembangan media pembelajaran komik manga digital berbasis android pada materi sistem hormon untuk kelas XI di MAN 2 Bandar Lampung yang memudahkan materi b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
2
0
4
Order By: Relevance
“…The digital comic products produced fall into the very feasible criteria with the details of the comic feasibility assessment as follows; the results of the material expert assessment are 94.38%, the media expert assessment is 89.34%, the learning expert assessment is 96%, the assessment based on the teacher's response is 93.22% and the results of the development trial for students in class XI IPA 2 are 92 ,38%. The results of this study are in accordance with the research of Haka & Suhanda (2018) where the results of media development fall into the criteria of being very suitable for use as learning media. The advantages of the developed product are that the product contains cell material that is presented systematically, contains interesting pictures and illustrations and has gone through validation process, which can be read anywhere and anytime.…”
Section: The Effect Of Digital Comics On Learning Outcomessupporting
confidence: 89%
See 1 more Smart Citation
“…The digital comic products produced fall into the very feasible criteria with the details of the comic feasibility assessment as follows; the results of the material expert assessment are 94.38%, the media expert assessment is 89.34%, the learning expert assessment is 96%, the assessment based on the teacher's response is 93.22% and the results of the development trial for students in class XI IPA 2 are 92 ,38%. The results of this study are in accordance with the research of Haka & Suhanda (2018) where the results of media development fall into the criteria of being very suitable for use as learning media. The advantages of the developed product are that the product contains cell material that is presented systematically, contains interesting pictures and illustrations and has gone through validation process, which can be read anywhere and anytime.…”
Section: The Effect Of Digital Comics On Learning Outcomessupporting
confidence: 89%
“…The presence of the internet should be used to improve the quality of learning. Haka & Suhanda (2018) state that technological developments in the field of education should be able to create a comfortable atmosphere in the learning process. However, Irwandi & Juriah (2016) reported that it turns out that educators have not optimally utilized the internet, especially in terms of using learning media.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the data collection such as interviews and observations of respondents who received offers to test this comic was carried out, to produce valid data according to the wishes of the market. (Haka and Suhanda, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Media dalam proses pembelajaran mempunyai peranan yang sangat penting dalam pendidikan. Materi yang disampaikan kegiatan pembelajaran dapat membantu menghadiri media sebagai perantara untuk mendapatkan hasil yang maksimal dan kualitas belajar siswa (Haka, 2020).…”
Section: Pendahuluanunclassified